El Niño–Southern Oscillation‐time scale covariation of sea surface salinity and freshwater flux in the western tropical and northern subtropical Pacific - Akira Nagano; Takuya Hasegawa; Iwao Ueki; Kentaro Ando (Geophysical Research Letters)
Abstract We examined the covariation of sea surface salinity (SSS) and freshwater flux in the western tropical and northern subtropical Pacific on the El Niño–Southern Oscillation time scale, using a canonical correlation analysis of monthly data between 2001 and 2013. The dominant covariation, i.e., the first canonical mode, has large positive and negative amplitudes in regions east of the Philippines and New Guinea, respectively, and reaches peaks in autumn to winter of El Niño years. The positive SSS anomaly east of the Philippines is advected to the Kuroshio Extension region. We found that the second canonical mode is another coupled variation with localized amplitudes of SSS under the atmospheric convergence zones in winter to spring of La Niña years. However, the negative SSS anomaly is annihilated possibly by the evaporation in the subtropical region.